Effect of Ethanol Addition as Extraction Solvent on The Content of Bioactive Materials in Dragon Fruit Skin Extract and Powder - Dian Shofinita; Yasid Bindar; Tjokorde Walmiki Samadhi; Arwinda Aprillia Jaelawijaya; Mifta Fawwaz (Reaktor, 2020)
This study aims to produce natural pigments for food prepared from dragon fruit skin by extraction and freeze-drying and to assess the effect of additional ethanol as extraction solvent on the process yield. During extraction stage, the effect of solvent (pure water and additional ethanol) on the yield of bioactive materials was assessed. Furthermore, during freeze-drying, the effect of maltodextrin addition as carrier agent on the quality of powder has also been evaluated. It has been found that the addition of ethanol as extraction co-solvent may give a positive effect on the yield of bioactive materials in the dragon fruit skin extracts, including the contents of anthocyanin, betacyanin, and total phenolic compounds. Regarding freeze drying, it was found that high recoveries of bioactive materials (84-92%) had been achieved, which indicates that freeze-drying may be suitable for drying such heat-sensitive materials. In addition, it was found that the addition of 10% maltodextrin as carrier agent may decrease the moisture content of the powder significantly, up to 8.162.12%, which is beneficial for its storage stability.Keywords: betacyanin; food additives; dragon fruit; extraction; anthocyanin.